1971
DOI: 10.1063/1.1660102
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of the Signal from the Laser Doppler Flowmeter: Time-Independent Systems

Abstract: A method for prediction of the spectrum observed with the laser Doppler flowmeter (LDF) is developed. A detailed analysis of the spectrum observed with steady flows is presented. The effects of diffusive motion of the scattering centers, spatially varying velocities, finite transit time of the centers through the sample volume, and uncertainty in scattering vector are computed. The latter two effects are shown to be identical. A computation of the sample volume size and shape is made using the optical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

1971
1971
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 16 publications
1
45
0
1
Order By: Relevance
“…By measuring the spectrum of the scattered light mixed with the incident light (heterodyne mode) it is possible to determine the mean velocity of the scattering centres in the scattering volume (Edwards et al 1971). The effect of velocity gradients and of random motionEI due to diffusion is to broaden the heterodyne spectrum, but these are second-order effects compared to the Doppler shift of the frequency which is cauf'ed by the mean motion of the particles in suspension.…”
Section: Theorymentioning
confidence: 99%
“…By measuring the spectrum of the scattered light mixed with the incident light (heterodyne mode) it is possible to determine the mean velocity of the scattering centres in the scattering volume (Edwards et al 1971). The effect of velocity gradients and of random motionEI due to diffusion is to broaden the heterodyne spectrum, but these are second-order effects compared to the Doppler shift of the frequency which is cauf'ed by the mean motion of the particles in suspension.…”
Section: Theorymentioning
confidence: 99%
“…Very little work has concerned the application of this technique in the presence of a flow [4][5][6]. Edwards et al [4] and Pike [5] showed that the mean velocity of the scattering centers can be accessed from the heterodyne mode of the scattering light whereas Fuller et al [6] showed that the homodyne mode leads to the determination of velocity gradients. A potential application is the determination of the transverse diffusion coefficient of polymer chains during flow.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed calculations of the spectrum for laminar pipe flow have been presented in a previous paper [1]. A typical spectrum is shown in figure 3.…”
Section: Theorymentioning
confidence: 99%
“…The instantaneous A.C. heterodyne current from the photodetector for a Laser Doppler Velocimeter may be written [1], assuming a constant ref-…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation